Hydroxypropyl-β-cyclodextrin improves the removal of polycyclic aromatic hydrocarbons by aerobic granular sludge. Issue 21 (19th September 2022) - Duan, Fu-ang; Wang, Juan; Ismail, Sherif; Sung, Shihwu; Cui, Zhaojie; Ni, Shou-Qing
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs) as polar organic pollutants, their potential harm to the environment has caused widespread concern. This study describes a simple method to prepare modified aerobic granular sludge (AGS) by hydroxypropyl-β-cyclodextrin (HP-β-CD). Using HP-β-CD modified AGS as the adsorbent, the removal of specific PAHs: Fluoranthene (Fla) reached 95% comparing to 80% of the unmodified AGS. The removal of Fla was related to initial concentration, temperature and ion concentration (Na +, Mg 2+ ). The removal efficiency of Fla reached 96.27%, 94.26% and 93.69%, when initial concentration of Fla was 10, 15 and 20 μmol/L. At temperatures of 15°C, 30°C and 45°C, the removal efficiency of Fla (15 μmol/L) gradually improved from 87.20% to 94.84% and 95.73%. The presence of Na + and Mg 2+ ions led to the deterioration of PAHs removal. With the increase of Na + and Mg 2+ concentrations, the removal efficiency of modified AGS on PAHs decreased by 3.9% and 6.5%, respectively . These findings indicate the potential application of cyclodextrins as the active sites of a complex modified polymer network for PAHs wastewater treatment. GRAPHICAL ABSTRACT: UF0001